Training needs of teachers of I and II basic general cycle, in natural sciences of educational centers of the Regional Office of the West, Alajuela - Barrantes Lobo, Teresa (2019)
This article is the product of a qualitative research, whose purpose was to identify the training needs of the teachers of the I and II General Basic cycle in the teaching of natural sciences. All the teachers of Basic General Education of the Regional Office of the Western District were considered to carry out the investigation. The technique used was the questionnaire, which was sent to all teachers. It was answered by 93 participants out of a total of 180 questionnaires. Twenty-six (26) training needs were identified in the areas of biodiversity, protected areas, physics, and chemistry. Based on this information, fourteen (14) trainingand updating workshops were given to twenty-two (22) teachers, on topics related to the cell, biodiversity, biological kingdoms, protected areas, magnetism, changes in the state of matter, chemical reactions, electrical circuits, energy, transformations of energy, solar energy, voltage and energy, and water uses. The main result of this process was that the teachers investigated and applied the methodological strategies that allowed the transmission or deepening of the knowledge in a pleasant and effective way.